Structure par espèces des captures de sparidés de la zone côtière de la Mauritanie (secteur cape timiris) pendant la période mai - juin 1982 - Maxim, Cornelia (Cercetări Marine - Recherches Marines, 2026)
The paper reviews the Sparides net in a coastal fishery in the Cape Timiris area, during May - June 1982, and the dominance of each species in the total catch. Can be remarked the dominance in number of specimens for Genus Diplodua and quantitative for Genus Spondyliosoma and Pagrus.